The reading contracts in the advertising discourse of health communication campaigns: an analysis of the “I know. Do you know?” campaign - Costa, Ana Cláudia; Barbalho, Arthur; Sousa, Suelayne; Lacerda, Juciano de Sousa; Molano, Mar Marcos; Ramos, Maria Natália; Muneiro, Lilian Carla (Brazilian Journal of Sexually Transmitted Diseases, 2021)
Introduction: In view of the syphilis epidemic that Brazil is experiencing and the need to strengthen the discourse on preventing this sexually transmitted infection (STI), the campaign “Eu sei, você sabe?” (I know. Do you know?) was conducted for dissemination of the pieces on social media. Objective: The of aim of this study was to perform a qualitative descriptive analysis of the posts published on the social network Instagram of the National Campaign to Fight Syphilis 2020-21 aimed at young people. Methods: The analysis performed was based on the method suggested by Eliseo Véron and aimed to establish relationships between the “reading contracts” offered and the processes of focusing (strong direct relevance) and defocusing (interdiscursive relevance) acting in the messages with the results of the communication indicator “Reach/Exposure”. Results: The analysis was conducted from October 2020 to April 2021. In all, 31 cards were published. Among them, eight publications presented in their content a discourse directed at young people including individuals in the 20-29 age bracket. In general, the pieces provided a common proposal of visual structuring and aimed to address the deficiencies identified in previous campaigns developed and presented in the perspective of the project itself, as well as the propositions established by control agencies for dealing with syphilis in Brazil. Conclusion: Some hypotheses raised on the basis of the analysis were as follows. There is the possibility that the distinction between grammars of production and recognition produce negotiations or resistance to the meaning of the interpellation contained in the theme “Sífilis. Eu sei. Você sabe?” Even if the characters presented in the cards did not include some specific audiences, such as young transgenders, the language offered can generate empathy in these audiences. The production strategies of cards with a more visual aesthetic and added to a predominantly graphic distribution of important information possibly contributed to a greater reach/impact on the social network audience.